Optical Reflections of the Theatrical Techniques and Their Impact on the Shows of Children's Theater - Al- Baglan, Mayada Majid Amin; Hashem Al-Shammari, Muhammad Kazem (Journal of Tikrit University for Humanities, 2020)
Children theater is a moral and educational value system that seeks to stimulate the child's interest through focusing on influential factors that work to attract and influence the child taking into account the behavioral and cognitive aspect of the child as a recipient and a small critic differs from the public or theatrical recipient. In terms of behavior and completeness of personality, visual reflections are considered as theatrical techniques not only represent color but a thought dealing with the logic of things in conjuring them on stage with the enhancement of the dramatic position effectively through attraction and communication. In order to make the child to follow the play we focus on the visual reflections that draw his/her attention. The child as a recipient does not seek to hear only, but to see, understand and search often, so we focus on the theatrical optics as elements scenography motion monolithic make him a vigilant follower. This research attempts to highlight the tools of expression, but in new formulations emphasize the design work, which in turn will establish the visual elements that are the basis of visual attraction to achieve social interaction and entertainment in the child.